SOSIALISASI BATAS USIA NIKAH SEBAGAI UPAYA PENCEGAHAN STUNTING - Sari, Widya; Supriyanto, Agus (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
The requirement of baligh or sufficient age in marriage is very important because from existing cases, many marriages are carried out by early childhood or those who are not old enough are very risky. The age of first marriage is one of the important factors that affect fertility and will end in the growth and development of children who fail or are called stunted. The purpose of community service is to reduce the high stunting rate of 17.8 in Bekasi Regency, one of which is Medalkrisna Village, Bojongmangu District. The target of community service participants is adolescents in Medalkrisna Village who are feared to be perpetrators of early marriage with the implementation method, namely community education in the form of socialization. With this service, it is hoped that the community can increase understanding regarding the negative impact of early marriage and prevent stunting. The results of the program show that this socialization activity went well and was successful in increasing knowledge related to the impact of early marriage based on an increase in the percentage of high categories in the post test.